Care Poverty When Older People's Needs Remain Unmet - Kröger, Teppo (Sustainable Development Goals Series, 2022)
"In this book, Teppo Kröger provides us with a new way of analysing inequalities associated with long-term care - this is a necessary and welcome contribution on care at a vital time". -Mary Daly, Professor, University of Oxford, United Kingdom This open access book turns the research attention of social policy scholars and long-term care researchers from comparative descriptions of care systems, focusing mostly on expenditures and volumes of long-term care services, to outcomes, and in particular to the question whether older people really receive the support that they need. Without knowledge about which needs and which social groups are currently inadequately covered, it is impossible to guide policy development. The book puts forward a novel theoretical framework to guide future research work and public discussion on the issue of unmet long-term care needs, by broadening the current discussion so that inadequate care is seen in its societal and policy contexts, taking structural issues and policy designs into account. Kröger outlines three different domains of care poverty (personal care poverty, practical care poverty and socio-emotional care poverty) and differentiates between main methods how unmet needs are measured. This book summarises the existing knowledge on the prevalence, factors and consequences of unmet care needs and interprets these comparatively in the light of social inequalities and care policy models of different welfare states. It will be invaluable to students and scholars of social policy, social work, social gerontology, sociology and political science, and to all disciplines across the field of social sciences that study welfare state policies and care for older people. Teppo Kröger is Professor of Social and Public Policy, Department of Social Sciences and Philosophy, University of Jyväskylä, Finland. .